İşletmelerde Yeni Performans Ölçümleme Sistemleri - (:unkn) unknown (My University, 2004)
Bu makale, performans Ölçümleme sistemleri olan Balanced Scorecard ve Tableau de Bord'u incelemektedir.Balanced Scorecard, finansal ve finansal olmayan stratejik ölçüleri birleştiren bir modeldir. Scorecard,vizyon ve stratejiyi ölçü ve amaçlara çevirmektedir. Bu sistem aynı zamanda stratejik yönetim kontrol tekniği olarakta kabul edilebilir. Organizasyonun stratejik amaçlarını performans gösterge setine dönüştüren Balanced Scorecard'ın dört temel perspektifi vardır. Bunlar, Finansal-Müşteri-içsel İş Süreçleri-Öğrenme ve Gelişmedir. Tableau de Bord, Fransa'da ortaya çıkmış ve 50 yıldır kullanılan bir sistemdir. Tableau de Bord, finansal ve finansal olmayan ölçülerden oluşan bir kumanda paneli ölçü setidir. Bu makale, Balanced Scorecard ile Tableau de Bord arasında temel benzerlik ve farklılıkları da içermektedir.

This paper examines the performance measurement systems; the Balanced Scorecard and the 'Tableau de Bord." The Balanced Scorecard is a model which integrates financial and non-financial strategic measures. The scorecard translates the vision and strategy into objectives and measures. The Balanced Scorecard can also considerate as a strategic management control tool. The Balanced Scorecard which translates an organization's strategic objectives into a set of performance indicators has four perspectives; Financial- Customer - Internal Business Process - Learning and Growth. The "Tableau de Bord" was introduced in France and has been used for at least 50 years The Tableau de Bord is a set of dashboard measures includes both financial and non financial strategic measures. This paper concludes that the main differences between "the Balanced Scorecard" and "the Tableau de Bord"
New Performance Measurement Systems in Organizations
Keywords: İktisat; Tarih; İşletme